2018
DOI: 10.14393/bj-v34n1a2018-39382
|View full text |Cite
|
Sign up to set email alerts
|

Chemical diversity of essential oils from Hyptis pectinata (L.) Poit

Abstract: ABSTRACT:The essential oils are secondary metabolites formed by several chemical compounds that confer to these substances great social and economic importance. This diversity of compounds is generally determined by the genetic constitution of the plant, although environmental factors may also influence the type, amount, and concentrations of the compounds present in the essential oil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…This event may be due to evaporation, oxidation, and the occurrence of undesirable changes during the time of storage [83,84]. Our results are in agreement with similar findings on Lemon balm (Melissa officinalis L.) [26], Hyptis pectinata [85], and Thymus daenensis [86]. It might be found that the EO keeps its original quality when stored at freezer temperature.…”
Section: Food Science and Engineering Volume 3 Issue 2|2022| 161supporting
confidence: 89%
“…This event may be due to evaporation, oxidation, and the occurrence of undesirable changes during the time of storage [83,84]. Our results are in agreement with similar findings on Lemon balm (Melissa officinalis L.) [26], Hyptis pectinata [85], and Thymus daenensis [86]. It might be found that the EO keeps its original quality when stored at freezer temperature.…”
Section: Food Science and Engineering Volume 3 Issue 2|2022| 161supporting
confidence: 89%
“…The DNA barcode can only authenticate the medicinal plant while the chemical profile provides information on the presence and concentration of compounds with pharmacological activity [ 63 ]. This diversity of compounds is generally determined by the genetic constitution of the plant, although environmental factors may also influence the type, amount, and concentrations of the compounds present in the essential oil [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…The genetic constitution generally determines the diversity of secondary metabolites produced by plants. However, various biotic and abiotic factors can alter the metabolic pathway of secondary metabolites, leading to the biosynthesis of distinct constituents of the oil, differing from the genetic profile [52,53] …”
Section: Resultsmentioning
confidence: 99%
“…However, various biotic and abiotic factors can alter the metabolic pathway of secondary metabolites, leading to the biosynthesis of distinct constituents of the oil, differing from the genetic profile. [52,53] Chemical and genetic correspondences were observed for the species Nectandra cuspidata and N. puberula. The essential oils of this subclade were rich in sesquiterpene hydrocarbons and characterized by the common presence of (E)-caryophyllene and bicyclogermacrene.…”
Section: Chemical and Genetic Diversity Of The Ocotea Complexmentioning
confidence: 95%